2007
DOI: 10.1038/sj.onc.1210646
|View full text |Cite
|
Sign up to set email alerts
|

p63(TP63) elicits strong trans-activation of the MFG-E8/lactadherin/BA46 gene through interactions between the TA and ΔN isoforms

Abstract: We report here that human MFGE8 encoding milk fat globule-EGF factor 8 protein (MFG-E8), also termed 46 kDa breast epithelial antigen and lactadherin, is transcriptionally activated by p63, or TP63, a p53 (TP53) family protein frequently overexpressed in head-and-neck squamous cell carcinomas, mammary carcinomas and so on. Despite that human MFG-E8 was originally identified as a breast cancer marker, and has recently been reported to provide peptides for cancer immunotherapy, its transcriptional control remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The level of p63 mRNA, already low in Hela control cells, was further reduced following NF-YA loss. At the protein level, we observed a decrease in ΔNp63, the only isoform we detected by Western blot in control cells (Supplementary Figure S5) [43, 44]. This result is consistent with the established role of NF-Y as transcriptional activator of the ΔNp63 promoter [45].…”
Section: Discussionsupporting
confidence: 86%
“…The level of p63 mRNA, already low in Hela control cells, was further reduced following NF-YA loss. At the protein level, we observed a decrease in ΔNp63, the only isoform we detected by Western blot in control cells (Supplementary Figure S5) [43, 44]. This result is consistent with the established role of NF-Y as transcriptional activator of the ΔNp63 promoter [45].…”
Section: Discussionsupporting
confidence: 86%
“…Autocrine MFG-E8 production by melanoma cells thereby constitutes an alterative scheme that might be more resistant to varying local conditions. Whereas the specific pathways that regulate MFG-E8 expression in cancer cells remain to be elucidated, p63 may be involved in some cases (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular mechanisms involved in the MFG-E8 up-regulation in cancer remain largely unknown. In an in vitro study using keratinocyte and a squamous cell carcinoma line [ 56 ], reporter gene assays using Mfge8 gene promoter regions and chromatin immunoprecipitation experiments showed that the transactivator (TA) isoforms of p63 activated Mfge8 transcription through a p53/p63 [ 57 ] motif at −370. Moreover, p63 siRNA treatment of the squamous carcinoma cells suppressed production of MFG-E8 protein, leading to suppression of the cell adhesion.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%